Evaluation of flocculation characteristics and biodegradation studies of reduced gum rosin and psyllium‐based hydrogel. Issue 6 (24th March 2020) - Wadhera, Priti; Jindal, Rajeev; Dogra, Rakesh
Abstract: Present study explored the swelling behavior, biodegradability and flocculation efficiency of hydrogel polymer based on renewable backbones‐psyllium and gum rosin. Swelling studies revealed that the polymer sample exhibit pH and temperature‐dependent swelling behavior. The polymer sample was assessed for its flocculation efficiency by optimizing the process parameters such as polymer dose, pH, and temperature. The polymer sample illustrated the maximum flocculation efficiency of 96% in 500 mg/L kaolin suspension under optimized experimental conditions. Investigation of biodegradation behavior was carried out using the soil burial and composting method. The percentage degradation of the polymer sample was observed to be 86.8% and 90.4% in 63 days using soil burial and composting method, respectively. The progress of biodegradation was analyzed through Fourier transform infrared and scanning electron microscopy techniques. Thus, the polymer sample was found to be cost effective, eco‐friendly, biodegradable material that has significant flocculation characteristics, and hence can be utilized for treatment of kaolinated wastewater.